EFFECTS OF MINERAL AND BIOHUMUS FERTILIZERS ON TOMATOES GROWN IN GREENHOUSES ON TYPICAL GRAY SOILS - Musurmonova Mukambar Pazitdinovna; Ruzmatova Sevinch Bakhtiyor qizi; Tolibjonova Dilsora Sanjar qizi; Esanova Mohinur Khurshid qizi (Journals Park Publishing, 2023)
Among the crops of our republic, tomatoes hold an important place, and they are widely grown in our country. Therefore, to meet the demand of the population for fresh fruits and the canning industry, it is necessary to increase the volume of tomato production. This can be achieved not only by creating new high-yielding varieties but also by improving the productivity through modern technologies of tomato cultivation.
Keywords: Rich in minerals, tomato cultivation in warm areas, improved quality of production.